Quantitative accuracy in total-body imaging using the uEXPLORER PET/CT scanner. (11th October 2021) - Leung, Edwin K; Berg, Eric; Omidvari, Negar; Spencer, Benjamin A; Li, Elizabeth; Abdelhafez, Yasser G; Schmall, Jeffrey P; Liu, Weiping; He, Liuchun; Tang, Songsong; Liu, Yilin; Dong, Yun; et al.
Abstract: Absolute quantification of regional tissue concentration of radioactivity in positron emission tomography (PET) is a critical parameter-of-interest across various clinical and research applications and is affected by a complex interplay of factors including scanner calibration, data corrections, and image reconstruction. The emergence of long axial field-of-view (FOV) PET systems widens the dynamic range accessible to PET and creates new opportunities in reducing scan time and radiation dose, delayed or low radioactivity imaging, as well as kinetic modeling of the entire human. However, these imaging regimes impose challenging conditions for accurate quantification due to constraints from image reconstruction, low count conditions, as well as large and rapidly changing radioactivity distribution across a large axial FOV. We comprehensively evaluated the quantitative accuracy of the uEXPLORER total-body scanner in conditions that encompass existing and potential imaging applications (such as dynamic imaging and ultralow-dose imaging) using a set of total-body specific phantom and human measurements. Through these evaluations we demonstrated a relative count rate accuracy of ±3%–4% using the NEMA NU 2-2018 protocol, an axial uniformity spread of ±3% across the central 90% axial FOV, and a 3% activity bias spread from 17 to 474 MBq 18 F-FDG in a 210 cm long cylindrical phantom. Region-of-interest quantification spread of 1% was found by simultaneously scanning three NEMA NU 2 image quality phantoms, as well as relatively stable volume-of-interest quantification across 0.2%–100% of total counts through re-sampled datasets. In addition, an activity bias spread of −2% to +1% post-bolus injections in human subjects was found. Larger bias changes during the bolus injection phase in humans indicated the difficulty in providing accurate PET data corrections for complex activity distributions across a large dynamic range. Our results overall indicated that the quantitative performance achieved with the uEXPLORER scanner was uniform across the axial FOV and provided the accuracy necessary to support a wide range of imaging applications.